2020
DOI: 10.1155/2020/6687358
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Stress- and Burnout-Related Factors of University Professors

Abstract: The aim of the present study was to analyse the gender differences in stress-related factors of university professors. A cross-sectional study was carried out, where gender differences in psychological, nutrition, physical activity, and oral health stress-related factors were analysed in 470 Spanish university professors (58.7% male and 41.3% female, 42.1 ± 9.2   years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
25
3
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 77 publications
10
25
3
6
Order By: Relevance
“…Regarding oral health, women had higher values for daily teeth brushing and no significant differences were found in dry mouth and gastritis variables. This higher frequency in daily tooth brushing corresponds with previous studies and may be linked to the higher values of neuroticism and conscientiousness shown by females [44,45].…”
Section: Discussionsupporting
confidence: 89%
“…Regarding oral health, women had higher values for daily teeth brushing and no significant differences were found in dry mouth and gastritis variables. This higher frequency in daily tooth brushing corresponds with previous studies and may be linked to the higher values of neuroticism and conscientiousness shown by females [44,45].…”
Section: Discussionsupporting
confidence: 89%
“…This circumstance has also been appreciated in previous studies [ 7 ]. It denotes that, despite the high levels of stress and burnout [ 39 ] among university professors, educational inclusion is not affected by years of professional experience. The commitment to inclusion is more present in the professors who are developing their professional careers (experience between 6 and 15 years).…”
Section: Discussionmentioning
confidence: 99%
“…Gender plays a meaningful function in the way in which work is experienced, rewarded, organized, not only in terms of work-related segregation, inequality in earnings, mobility, work status, but also in work behavior, social relations, and attitudes (Wharton, 2013). A cross-sectional study carried out among Spanish university professors analyzed gender differences in stress and burnout-related factors and showed up that female professors reported a higher burnout perceived by emotional exhaustion, neuroticism, and stress than males (Redondo-Flórez et al, 2020).…”
Section: Theoretical Background Of Burnout Syndrome In Terms Of Gende...mentioning
confidence: 99%